Production of Secondary Metabolite Compounds of Gotu Kola (Centella asiatica) Under Salinity and Drought Stress - Amallia, Nur; Mas’ud, Zainal Alim; Ratnadewi, Diah (Jurnal Jamu Indonesia, 2020)
Gotu kola (Centella asiatica) is a traditional herbal plant that has been reported have a variety of pharmacological activities. The compounds of gotu kola that play a role on pharmacological activities are triterpene group compounds, namely madecasosside (MD), asiaticoside (AS), madecassic acid (AM), and asiatic acid (AA). Stress can affect the production of biomass and secondary metabolite compounds in plants. The aims of the study is to analyze the effect of salinity and drought stress on biomass and 4 compounds of triterpene in gotu kola. Harvesting is done when the plant is 8 weeks old. The yield of the biomass was analyzed and then extracted using methanol solvent to be analyzed secondary metabolite levels using the high performance liquid chromatography (HPLC) method. The lowest crop biomass was obtained at 50% of field capacity and 3,000 ppm salt content. The highest levels of MD and AS were established in conditions of 100% field capacity and 1,000 ppm salt content. The 50 and 100% field capacity and 1,000-3,000 ppm salt content did not affect the levels of AM and AA.